Improving strategic management through risk analysis: small palm (Elaeis guineensis) oil industrializers, Central America - Paniagua-Molina, Javier (2020)
Introduction. Palm cultivation allows oil to be obtained for human and industrial consumption. Some of its development has been achieved through associations of agricultural producers, who have had access to financing to build industrial plants for oil extraction and refinement, which is of great importance to the economy developing countries. Objective. To demonstrate how strategic and risk management influence the profitability and value of the small palm oil industrializer business. Materials and methods. Financial, technical, market, and production indicators were used in a price forecast model. The Monte Carlo simulation method was performed and a time series model was fitted to forecast the international price of palm oil. Subsequently, a univariate structural econometric model was adjusted to forecast revenue based on international price and other variables. Finally, a parameterized cash flow was developed that incorporated the results of the previous models to estimate the value of the business. Results. The international oil price forecast showed high volatility that directly affected the organization’s revenue forecasts and conveyed its effect to cash flows. The value of the business and equity was negative, and in the face of debt restructuring scenarios and the elimination of unproductive assets, they improved considerably. Conclusion. Low-diversified palm oil production companies had a high exposure to changes in international prices which, together with high levels of debt for fixed asset investments with long recovery periods, affect their cash flow, the value of the company, and its assets.